Comparative risk of pulmonary adverse events with transfusion of pathogen reduced and conventional platelet components. Issue 7 (24th June 2022) - Snyder, Edward L.; Wheeler, Allison P.; Refaai, Majed; Cohn, Claudia S.; Poisson, Jessica; Fontaine, Magali; Sehl, Mary; Nooka, Ajay K.; Uhl, Lynne; Spinella, Philip; Fenelus, Maly; Liles, Darla; et al.
Abstract: Background: Platelet transfusion carries risk of transfusion‐transmitted infection (TTI). Pathogen reduction of platelet components (PRPC) is designed to reduce TTI. Pulmonary adverse events (AEs), including transfusion‐related acute lung injury and acute respiratory distress syndrome (ARDS) occur with platelet transfusion. Study design: An open label, sequential cohort study of transfusion‐dependent hematology‐oncology patients was conducted to compare pulmonary safety of PRPC with conventional PC (CPC). The primary outcome was the incidence of treatment‐emergent assisted mechanical ventilation (TEAMV) by non‐inferiority. Secondary outcomes included: time to TEAMV, ARDS, pulmonary AEs, peri‐transfusion AE, hemorrhagic AE, transfusion reactions (TRs), PC and red blood cell (RBC) use, and mortality. Results: By modified intent‐to‐treat (mITT), 1068 patients received 5277 PRPC and 1223 patients received 5487 CPC. The cohorts had similar demographics, primary disease, and primary therapy. PRPC were non‐inferior to CPC for TEAMV (treatment difference −1.7%, 95% CI: (−3.3% to −0.1%); odds ratio = 0.53, 95% CI: (0.30, 0.94). The cumulative incidence of TEAMV for PRPC (2.9%) was significantly less than CPC (4.6%, p  = .039). The incidence of ARDS was less, but not significantly different, for PRPC (1.0% vs. 1.8%, p  = .151; odds ratio = 0.57, 95% CI: (0.27, 1.18). AE, pulmonary AE, and mortality were not different between cohorts. TRs were similar for PRPC and CPC (8.3% vs. 9.7%, p  = .256); and allergic TR were significantly less with PRPC ( p  = .006). PC and RBC use were not increased with PRPC. Discussion: PRPC demonstrated reduced TEAMV with no excess treatment‐related pulmonary morbidity.